Land Transformations in Ukraine: Problems and Expectations - Yuriy Hubeni; Volodymyr Krupa (Zeszyty Naukowe Szkoły Głównej Gospodarstwa Wiejskiego w Warszawie. Problemy Rolnictwa Światowego)
The analysis of urgent problems of land relations transformation and of forming agricultural land market in Ukraine is carried out in the article. The general characteristic of main reform stages is given. The reasons of lasting action of the moratorium on agricultural land sale-purchase being the chief obstacle for complete market development are defined. Supporters' and opponents' arguments about moratorium canceling, population estimation of advantages and threats of land circulation are described. The results of the research project "Farmers' land expectation" made by the authors are given. The project purpose was studying population rational expectations concerning the directions of further land reform development and its results. The research was conducted on the local level in rural surrounding, which is characterized by high competition level among agrarian business subjects at agricultural land lease market. Landowners' and other interested group people' opinions concerning lease cost, potential sale price, inclination towards land sale, possibilities of farmers' common farming on their own land, leaseholders' participation in social and economic development of rural areas are examined. High level of farmers' uncertainty about land market indicators because of knowledge lack and low level of land reform information support is established.